Biotechnology and Plant Breeding Applications and Approaches for Developing Improved Cultivars - Borém, Aluízio; Ed. Fritsche-Neto, Roberto; Ed (Academic Press is an imprint of Elsevier, 2014)
This book discusses applications of biotechnology in plant breeding. It covers key topics such as biometry applied to molecular analysis of genetic diversity and genetically modified plants, and goes beyond recombinant DNA technology to bring together key information and references on new biotech tools for cultivar development.